De l’île de Majorque au désert du Sahara : réseaux de commerce juifs et trafic du cuivre vers 1400 - Ingrid Houssaye Michienzi (Revue des Mondes Musulmans et de la Méditerranée)
The robbery, in the Tuat, of a cargo full of copper sent from Majorca by Florentine merchants put in light the trade circulations between the Mediterranean and the Sahara at the very beginning of the 15th century. For its rich content, the correspondance kept between agents of different Datini subsidiaries fills an important gap in the documentation on the Tuat and its connections. Indeed, it shows which were the main itineraries and the actors of this trade, illustrating the role of Jewish merchants circulating along the road Majorca-Honein-Tuat, which became the privileged access to reach Saharan and Subssaharan markets. This article aims to reveal the issues and the modalités of such a trade.